2019
DOI: 10.1167/iovs.18-26354
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of Disc-Fovea Raphe Angles Determined by Optical Coherence Tomography and MP-3 Microperimetry in Eyes With a Glaucomatous Hemifield Defect

Abstract: The purpose of this study was to evaluate the concordance of a temporal raphe architecture estimated using optical coherence tomography (OCT) and MP-3 microperimetry. METHODS. We enrolled 25 eyes with either an upper or lower glaucomatous hemifield defect, as detected on the Humphrey visual field 30-2 test. A structural temporal raphe was extrapolated from visible end points of retinal nerve fiber bundles present in a perimetrically normal hemiretina on an en face Spectralis OCT image. A functional temporal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…A recent report 21 showed that the horizontal raphe in the temporal macular area was different from the fovea-disc line. Another study 22 reported that the structural temporal raphe was more deviated to the perimetrically normal hemiretinal side than to the functional temporal raphe in eyes with a glaucomatous hemifield defect. A third limitation is that there were only five patients in which we captured OCT data prior to the appearance of glaucomatous changes to the fundus which could be used to demonstrate that the appearance of asymmetry in retinal thickness revealed by OCT is an initial sign of glaucoma onset.…”
Section: Discussionmentioning
confidence: 96%
“…A recent report 21 showed that the horizontal raphe in the temporal macular area was different from the fovea-disc line. Another study 22 reported that the structural temporal raphe was more deviated to the perimetrically normal hemiretinal side than to the functional temporal raphe in eyes with a glaucomatous hemifield defect. A third limitation is that there were only five patients in which we captured OCT data prior to the appearance of glaucomatous changes to the fundus which could be used to demonstrate that the appearance of asymmetry in retinal thickness revealed by OCT is an initial sign of glaucoma onset.…”
Section: Discussionmentioning
confidence: 96%
“…Mean subject age was 25 years (range, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and spherical equivalent (SE) ranged from 0D to À13D (minimum 10 subjects per 1D range of refraction between 0D to À5D; 27 subjects in the range À3 to À6D; 17 subjects beyond À6D). Axial length and vitreous chamber depth (VCD) were measured by A-scan ultrasonography (AL-100 biometer; Tomey GmbH, Nürnberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…18 Hence, the anatomy of the temporal raphe may be relevant to improving the assessment of glaucoma. 11,13,14,[18][19][20][21][22] Furthermore, the low density of RNFL bundles in this area may enable direct visualization of changes to bundle density. Glaucomatous deficits occur characteristically in this region, which corresponds to the nasal step of the visual field.…”
mentioning
confidence: 99%
See 1 more Smart Citation